IDEAL STEERING IN ACCUMULATIVE NUMEROUS HUBBED NETWORK SYSTEMS - Sriram, Gunnam; B. Nagasri, Ms. (International Journal of Psychosocial Rehabilitation, 2020)
Networking means creating communication between two or more systems. The main purpose of networking is distributing and sharing data and devices between other devices. Networks are constructed by using software and hardware. The communication can be wired or wireless. In wired communication, the data will be transferred by using a physical medium like cables. The other mode of communication is wireless mode. In this wireless communication, data can be transferred from one device to another device logically. In wireless transmission, the microwave and radio frequencies are used to make a communication. Wireless communication means creating a communication between one source device and another destination device, or a number of destination devices are connected by using various ways. Each device is called a node. Every node is connected to other nodes by using a set of signals. The actual messages are encrypted on the sender side before transmitting the data. The encrypted data is transmitted to the receiver through transmission medium. On the receiver side, the received data is decrypted before the messages are displayed to the user using some algorithms. In wireless communication, finding a proper path is a very difficult task. This paper describes how to find the optimum path from source device to destination device in a multi-hop network with less energy consumption. In this system, the Floyd-Warshall algorithm is used to find the most favorable path with the least amount of energy. With the single time of execution, this algorithm finds the less-distance path. During data transmission, there is a chance to lose the data packets.